Ovarian Hyperstimulation: Diagnosis, Prevention, and Management - Levi-Setti, Paolo Emanuele; Di Segni, Noemi; Gargasole, Clara; Ronchetti, Camilla; Cirillo, Federico (Seminars in Reproductive Medicine, 2021)
Ovarian hyperstimulation syndrome (OHSS) is a severe complication of controlled ovarian stimulation (COS). Pathogenesis of the disease is based on massive transudation of protein-rich fluid from the vascular compartment into the peritoneal, pleural and pericardial spaces, with a variable picture of clinical manifestations depending on its severity. Nowadays OHSS can easily be avoided by several prevention methods, ranging from identification of high-risk patients, choice of a correct protocol stimulation, trigger with gonadotropin-releasing hormone (GnRH) agonists or, finally, the freeze-all strategy. When OHSS occurs, it can usually be managed as outpatient care. Only if severe/critical cases are diagnosed hospitalization is necessary for appropriate rehydration, monitoring of fluid balance and eventual drainage of ascitic fluid. One of the most dangerous complications of OHSS is venous thromboembolism (VTE). Thromboprophylaxis has shown to be cost effective and widely used, while there are controversies regarding the usage of low dose aspirin (LDA) as a preventive measure.
Keywords: ovarian hyperstimulation syndrome; assisted reproduction technologies; diagnosis; prevention; management